Analysis and Application of Min-Cost Transition Systems to Business Process Management - Feng, Xiwen; Han, Dong; Tian, Yinhua (Computing and Informatics, 2020)
To improve the efficiency of conformance checking in process mining, new alignment approaches are presented between event logs and process models based on the min-cost transition systems of Petri nets. An algorithm is presented to obtain the transition system with the minimum cost based on the product of the event net and process net. The min-cost transition system is a directed acyclic graph, where the paths from the initial node to the final node include all optimal alignments between the trace and the process model based on the given cost function. Two algorithms are proposed to calculate an optimal alignment and all optimal alignments, respectively. All algorithms are implemented in ProM platform. After a series of the simulation experiments, the feasibility and effectiveness of the proposed approaches are illustrated.